Implementasi Perda Kota Surabaya Nomor 9 Tahun 2014 Tentang Penyediaan Ruang Bagi Pedagang Kaki Lima Di Masjid Al Akbar Kota Surabaya - Maharani Alvika Sari; Achluddin Ibnu Rochim; Rachmawati Novaria (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The existence of street vendors at the Al-Akbar Mosque in Surabaya City who sell and buy their goods without complying with existing regulations can cause traffic jams for road users, those who are going to the hospital via the toll road or who have business via the toll road will have difficulties, because of the congestion. traders and buyers who park illegally. De to this incident, the Surabaya city government relocated the traders around the Al-Akbar Mosque to move to the Jambangan People's Market which is on the north side of the Al-Akbar Mosque. The purpose of this research is to provide a description and overview and also analyze the implementation of the Surabaya City Regional Regulation No. 9 of 2014 which discusses the provision of space for street vendors, not only to identify the supporting and inhibiting factors contained in the Regional Regulation policy. Surabaya City No. 9 of 2014. In this research, the method used is a research method by conducting observations, interviews and also documentation as evidence. The results of the research show that the implementation of the arrangement for street vendors is considered to be good but there are still inhibiting factors caused by the decline in the economic condition of the vendors after being relocated.